Energy diplomacy as a repositioning strategy Indonesia's geopolitics in the Arab World - Nur Kumalatuz Zahroh (Economic Military and Geographically Business Review, 2026)
Background: The Arab world is undergoing a fundamental transformation in its geopolitical and energy landscape as global dependence on fossil fuels declines and green energy transitions accelerate, reshaping regional power configurations and opening new opportunities for non-Middle Eastern actors. This study aims to analyze how global energy transformation and shifting Arab geopolitics reconfigure regional power structures and to formulate strategic pathways for Indonesia to reposition its foreign policy through energy diplomacy. Previous scholarship highlights energy as not merely an economic commodity but a strategic instrument of power, emphasizing the rise of energy diplomacy and governance in defining global influence. Methods:  This research employs a qualitative, descriptive-analytical method, combining literature review, policy document analysis, and geopolitical mapping to assess regional dynamics, Indonesia–Arab relations, and multilateral energy frameworks, particularly the role of the OPEC. Findings: The findings indicate that the transition towards renewable energy in Gulf countries has transformed energy from a trade-based asset into a model of political leverage, while Indonesia remains constrained by fragmented and largely bilateral energy diplomacy. The analysis shows that Indonesia’s suspended participation in OPEC limits its access to strategic energy governance networks and emerging green energy funding mechanisms, reducing its bargaining power in global energy forums. The theoretical framework of energy as a source of geopolitical power is substantiated by empirical evidence demonstrating that countries actively shaping energy governance gain greater diplomatic leverage and strategic depth. Conclusion: The study concludes that proactive energy diplomacy and strategic re-engagement with multilateral energy institutions are essential for strengthening Indonesia’s geopolitical role. Novelty/Originality of this article: The novelty of this article lies in conceptualizing Indonesia not merely as an energy consumer or market actor but as a potential “bridge state” in the emerging architecture of Islamic world energy diplomacy and green energy governance, integrating state-led and non-state diplomatic pathways.